Modeling of morphology of semiconductor surfaces with quantum nanowires - Zhanabaev, Z.Zh.; Grevtseva, T.Yu.; Imanbayeva, A.K.; Zhanabayeva, A.E. (Publishing House of the KarSU named after E.A.Buketov, 2014)
A possibility to model morphology of surfaces of semiconductor films containing quantum-sized structures is analyzed. For this aim we use our new map for fractal evolution of measure and method for reconstruction of dynamical chaos by one-dimensional sequence of data. Intermittent distribution of concentration of current carriers typical for images of semiconductor surfaces obtained by modern methods of microscopy was obtained. Distribution of current carriers is presented in phase plane. Using of the approach give us a possibility to model semiconductor surfaces containing horizontal and vertical quantum nanowires.
Keywords: morphology; semiconductor films; dynamical chaos; quantum-sized structure; map for fractal evolution; quantum nanowires